2015
DOI: 10.1021/es504710p
|View full text |Cite
|
Sign up to set email alerts
|

Emission of Titanium Dioxide Nanoparticles from Building Materials to the Environment by Wear and Weather

Abstract: In the present work, we investigate the effect of weathering duration on a commercial photocatalytic nanocoating on the basis of its nanoparticle emission tendency into two media, air and water. It is found that increased weathering duration results in stepwise structural deterioration of the nanocoating, which in turn decreases the nanocoating life, changes the nanocoating removal mechanism, and increases the particle emission concentration. Emission of free TiO2 nanoparticles is found to be weathering durati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
50
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 98 publications
(51 citation statements)
references
References 35 publications
0
50
1
Order By: Relevance
“…The study confirms the ability to alter the chemistry of the nano-enabled product in order to limit the loss of embedded NMs along the life cycle. [15][16][17][18]…”
Section: Iia Crystalline Nanocellulose (Cnc)mentioning
confidence: 99%
“…The study confirms the ability to alter the chemistry of the nano-enabled product in order to limit the loss of embedded NMs along the life cycle. [15][16][17][18]…”
Section: Iia Crystalline Nanocellulose (Cnc)mentioning
confidence: 99%
“…For example, the majority (more than 75%) of ENMs used in cosmetics—such as titanium dioxide (TiO 2 ), zinc oxide (ZnO), iron (Fe), aluminum oxide (Al 2 O 3 ), and nanoclays—are estimated to be released during use (Keller et al 2013). Similarly, ENMs used in outdoor applications (e.g., silver [Ag] and TiO 2 used in exterior paints and coatings) are expected to be released throughout their lifetime (Kaegi et al 2010, 2008a; O'Brien & Cummins 2010), although some studies have shown minimal or no release over short time scales (Shandilya et al 2015, Al‐Kattan et al 2013) and others have shown that the ENMs attach to organic binders and are released as aggregates rather than individual nanoparticles (Kaegi et al 2010). Conversely, ENMs used in batteries and electronics—such as copper (Cu), quantum dots, and silicon dioxide (SiO 2 )—have a much lower likelihood of entering the environment because they rarely come in contact with water and are strongly bound in the product matrix (Che et al 2014, Kim et al 2014, Kubota et al 2014, Zhang et al 2012, Takahashi et al 2011).…”
Section: Sources Of Enms In the Environmentmentioning
confidence: 99%
“…Kaegi et al 2008;Göhler et al 2010;Shandilya et al 2014). Shandilya et al (2015) showed that surface deterioration of the nanocoated samples was a function of the duration of weathering by ultraviolet light, temperature, and water. The results of Al-Kattan et al's (2013) study of artificial weathering indicate that the risk of release of TiO 2 particles into the environment is generally low, but an increase was observed when TiO 2 pigment containing paint was applied on rough surfaces (e.g.…”
Section: Source Of Tio 2 Particlesmentioning
confidence: 99%